Malingering of disabling mental illness to obtain a temporary work disability benefit: detection and morphology - Amado, Bárbara G.; Vilariño, Manuel; Mainar, Magdalena; Ágreda, Irene (Anales de Psicología / Annals of Psychology, 2025)
Background/Objective: In psychological assessments where the results may lead to obtaining some benefit or gain, malingering should be suspected. This is the case for temporary work disability due to psychological causes, for which high prevalence of malingering have been estimated. Therefore, a study was designed to examine the utility of the SCL-90-R in detecting malingered psychopathology motivated by the external incentive of obtaining a temporary work disability. Method: A total of 182 participants completed the SCL-90-R in a simulation design, under two conditions: responding under standard instructions and under instructions for malingering of psychological cause to obtain a temporary work disability. Results: The results revealed that the working population is almost entirely capable of malingering both clinical symptoms and mental disorders with sufficient severity to obtain a temporary work disability (secondary gain). They employed two strategies: indiscriminant symptom endorsement (malingering impairment across all clinical dimensions, even greater than the psychiatric population) and symptom severity (malinger an extreme intensity, even greater than the psychiatric population). Finally, it was found that the gender factor does not play a significant role in malingering. Conclusions: The implications of the results for forensic assessments are discussed.